Quo Vadis Urogynecology 2020 – Innovative Treatment Concepts for Urinary Incontinence and Pelvic Organ Prolapse - Naumann, Gert (Geburtshilfe und Frauenheilkunde, 2021)
The current treatment for urinary incontinence and pelvic organ prolapse includes a wide range of innovative options for conservative and surgical therapies. Initial treatment for pelvic floor dysfunction consists of individualized topical estrogen therapy and professional training in passive and active pelvic floor exercises with biofeedback, vibration plates, and a number of vaginal devices. The method of choice for the surgical repair of stress urinary incontinence consists of placement of a suburethral sling. A number of different methods are available for the surgical treatment of pelvic organ prolapse using either a vaginal or an abdominal/endoscopic approach and autologous tissue or alloplastic materials for reconstruction. This makes it possible to achieve optimal reconstruction both in younger women, many of them affected by postpartum trauma, and in older women later in their lives. Treatment includes assessing the patientʼs state of health and anesthetic risk profile. It is important to determine a realistically achievable patient preference after explaining the individualized concept and presenting the alternative surgical options.Die aktuelle Behandlung von Harninkontinenz und Genitalprolaps umfasst vielfältige innovative Möglichkeiten konservativer und operativer Therapien. Eine angepasste lokale Estrogenisierung und professionelle Techniken des passiven und aktiven Beckenbodentrainings mit Biofeedback, Rüttelplatte und verschiedenen Vaginaldevices stellen den Behandlungsbeginn bei Beckenbodenfunktionsstörungen dar. Methode der Wahl zur operativen Sanierung der Belastungsinkontinenz ist die Einlage einer suburethralen Schlinge. Die operative Behandlung des Genitalprolaps bietet verschiedene Methoden auf vaginalem oder abdominal/endoskopischem Weg unter Eigengewebsrekonstruktion oder Nutzung von alloplastischem Material. So gelingt eine individuelle optimale Rekonstruktion sowohl bei der jungen Frau mit zumeist postpartalen Schädigungen bis hin zur betagten Patientin in der letzten Lebensphase. Dazu gehört die Einschätzung des gesundheitlichen Zustandes der Patientin und dem bestehenden anästhesiologischen Risikoprofil. Wichtig ist die Ermittlung des realistischen Patientenwunsches nach Erläuterung eines individuellen Konzeptes und Darstellung auch alternativer operativer Möglichkeiten.
Keywords: stress incontinence; suburethral sling; pelvic organ prolapse; sacrocolpopexy; vaginal uterine fixation